ECONOMIC CONTRIBUTION OF DR. BABASAHEB AMBEDKAR (International Journal of Food and Nutritional Sciences, 2023)
The architect of the Indian Constitution, the leader who advocated for the rights of the untouchables, and worked towards abolishing the caste system, Dr. Babasaheb Ambedkar has made significant contributions to economic thought and economics. Dr. Babasaheb has addressed important economic issues such as energy and water planning, agriculture, taxation, industrial matters, and social justice. Therefore, studying his work has become essential today."